Trajectory of Mortality and Health-Related Quality of Life Morbidity Following Community-Acquired Pediatric Septic Shock - Zimmerman, Jerry J; Banks, Russell; Berg, Robert A; Zuppa, Athena; Newth, Christopher J; Wessel, David; Pollack, Murray M; Meert, Kathleen L; Hall, Mark W; Quasney, Michael; Sapru, Anil; Carcillo, Joseph A; et al. (Critical care medicine, 2020)
In-hospital pediatric sepsis mortality has decreased substantially, but long-term mortality and morbidity among children initially surviving sepsis, is unknown. Accordingly, the Life After Pediatric Sepsis Evaluation investigation was conducted to describe the trajectory of mortality and health-related quality of life morbidity for children encountering community-acquired septic shock. Prospective, cohort-outcome study, conducted 2013-2017. Twelve academic PICUs in the United States. Critically ill children, 1 month to 18 years, with community-acquired septic shock requiring vasoactive-inotropic support. Demographic, infection, illness severity, organ dysfunction, and resource utilization data were collected daily during PICU admission. Serial parent proxy-report health-related quality of life assessments were obtained at baseline, 7 days, and 1, 3, 6, and 12 months following PICU admission utilizing the Pediatric Quality of Life Inventory or Stein-Jessop Functional Status Scale. Among 389 children enrolled, mean age was 7.4 ± 5.8 years; 46% were female; 18% were immunocompromised; and 51% demonstrated chronic comorbidities. Baseline Pediatric Overall Performance Category was normal in 38%. Median (Q1-Q3) Pediatric Risk of Mortality and Pediatric Logistic Organ Dysfunction scores at PICU admission were 11.0 (6.0-17.0) and 9.0 (6.0-11.0); durations of vasoactive-inotropic and mechanical ventilation support were 3.0 days (2.0-6.0 d) and 8.0 days (5.0-14.0 d); and durations of PICU and hospital stay were 9.4 days (5.6-15.4 d) and 15.7 days (9.2-26.0 d). At 1, 3, 6, and 12 months following PICU admission for the septic shock event, 8%, 11%, 12%, and 13% of patients had died, while 50%, 37%, 30%, and 35% of surviving patients had not regained their baseline health-related quality of life. This investigation provides the first longitudinal description of long-term mortality and clinically relevant, health-related quality of life morbidity among children encountering community-acquired septic shock. Although in-hospital mortality was 9%, 35% of survivors demonstrated significant, health-related quality of life deterioration from baseline that persisted at least 1 year following hospitalization for septic shock.